PENGARUH KOMPETENSI KEPRIBADIAN GURU TERHADAP MINAT BELAJAR DAN PERSEPSI SISWA MADRASAH ALIYAH PADA PRESTASI BELAJAR SOSIOLOGI DI SERANG BANTEN - Rachmatullah Jundi; Muhamad Hanif Ramadhan (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of teacher personality competence on learning interest and students' perceptions of Madrasah Aliyah on sociology learning achievement. is to find out (1) the effect of student learning interest on sociology learning outcomes, (2) the effect of student perceptions of teacher personality competence on sociology learning outcomes, (3) the influence of student learning interest and student perceptions of teacher personality competence on sociology learning outcomes together -The same. The research method used was a survey with multiple linear analysis techniques. Test the hypothesis using multiple linear tests. The results of the study concluded that there was a significant influence of students' learning interest and students' perceptions of the teacher's personality competence together on sociology learning achievement. This is evidenced by the acquisition of Sig. 0.000 < 0.05 and Fh = 10.778. There is a significant influence of students' learning interest on sociology learning achievement of MA Private MA students in Serang Banten. This is evidenced by the acquisition of Sig. 0.005 < 0.05 and th = 2.934e